Synthesis of Electrical Conductive Metal-Organic Frameworks for Electrochemical Applications - Syed Shoaib, Ahmad Shah; Muhammad Altaf, Nasir; Azhar, Mahmood; Manzar, Sohail; Aziz, ur Rahman; Muhammad Khurram, Tufail; Tayyaba, Najam; Muhammad Sufyan, Javed; Sayed, M. Eldin; Md Rezaur, Rahman; Mohammed, M. Rahman (The Chemical Society of Japan & Wiley-VCH GmbH., 2024)
Electrical conductivity is very important property of nanomaterials for using wide range of applications especially energy applications. Metal-organic frameworks (MOFs) are notorious for their low electrical conductivity and less considered for usage in pristine forms. However, the advantages of high surface area, porosity and confined catalytic active sites motivated researchers to improve the conductivity of MOFs. Therefore, 2D electrical conductive MOFs (ECMOF) have been widely synthesized by developing the effective synthetic strategies. In this article, we have summarized the recent trends in developing the 2D ECMOFs, following the summary of potential applications in the various fields with future perspectives.